The Relationship Between Leadership Style and Work Motivation with Burnout Syndrome in Nurses during the Covid 19 Pandemic - Soliha Soliha; Rahmad Septian Reza (Universitas STRADA Indonesia, 2021)
The high number of patients, inadequate hospital facilities, and the high risk of exposure to diseases during the covid 19 pandemic make nurses experience Burnout syndrome. This research is a correlational analysis with a cross sectional approach. A population of 60 respondents with simple random sampling techniques. Independent variables are leadership styles and work motivation, while variable dependencies are burnout syndrome in nurses. Instrument research using the Maslach Burnout Syndrome Inventory (MBI) questionnaire. Analysts test used Kendall's tau_b and Spearman Rank test with @=0.05. The results showed that 55% of respondents aged 31-40 years, 90% of marital status, 55% of female sex, 53,3% of Ners education level and 56.6% length of work more than 10 years. Statistics test showed there was a relationship between leadership style and burnout syndrome in nurses with test results (p=0.047 < @=0.05).